MICROENCAPSULATION OF BIOACTIVE COMPOUNDS BY EXTRUSION METHOD - Etchepare, Mariana Araújo (2015)
The development of functional foods by adding bioactive faces many hurdles in the production of new foods. Microencapsulation is a useful tool to facilitate the protection of these compounds in foods, in particular, probiotics, vitamins, minerals, fatty acids, etc. Various microencapsulation methods have been used in order to improve the use of these ingredients promoting the successful delivery of these bioactive substances in the gastrointestinal tract. Among the microencapsulation techniques bioactive compounds, extrusion has been employed to obtain microparticles. In this review we will discuss topics regarding bioactive compounds and how to improve its stability through microencapsulation, emphasizing the method and studies on the extrusion technique.